Thinking about movies watching, questioning, enjoying - Lehman, Peter (Wiley, 2018)
This book is a thorough overview of movie analysis designed to enlighten both students and enthusiasts, and heighten their enjoyment of films. Readers will delve into the process of thinking about movies critically and analytically, and find how doing so can greatly enhance the pleasure of watching movies. Divided roughly into two parts, the book addresses film studies within the context of the dynamics of cinema, before moving on to a broader analysis of the relationship of films to the larger social, cultural, technological, and industrial issues informing them.